2015
DOI: 10.1139/apnm-2014-0538
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract supplementation does not hamper endurance-training adaptation but improves antioxidant capacity in sedentary men

Abstract: Abstract:The purpose of this study was to investigate the effect of green tea extract (GTE) supplementation combined with endurance training on endurance capacity and performance in sedentary men. Forty untrained men (age: 20 ± 1 years) participated in this study. Subjects were assigned to 1 of 4 treatments: (i) placebo-control (CTRL), (ii) GTE, (iii) endurance training (Ex), and (iv) endurance training with GTE (ExGTE). During the 4-week intervention, exercise training was prescribed as 75% oxygen uptake rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 42 publications
2
55
1
1
Order By: Relevance
“…Regarding CK release, no differences between groups were detected. One explanation for this result is the timing of sample collection; the literature reports that, even with intense exercise, high levels of CK may not be detected when sample collection occurs after 24 h following the last training session [49]. TRAP serum results revealed that the ET group had higher antioxidant capacity compared to both sedentary groups, increasing more than twofold (Figure 1A), which agrees with the literature [50].…”
Section: Discussionsupporting
confidence: 87%
“…Regarding CK release, no differences between groups were detected. One explanation for this result is the timing of sample collection; the literature reports that, even with intense exercise, high levels of CK may not be detected when sample collection occurs after 24 h following the last training session [49]. TRAP serum results revealed that the ET group had higher antioxidant capacity compared to both sedentary groups, increasing more than twofold (Figure 1A), which agrees with the literature [50].…”
Section: Discussionsupporting
confidence: 87%
“…Supplementing green tea extract during ten weeks of moderate-intensity endurance training in healthy males resulted in greater fat oxidation while cycling at 55% VO2peak, with no changes observed in the placebo group [109] (Table 4). Untrained men who performed a 4-week training intervention with green tea extract or placebo had similar improvements in VO2max and run to exhaustion time (8.1-9.7 km/h at 18-20% grade), with no differences between groups for total antioxidant status [153]. However, these are performance tasks that would not be expected to benefit from increased fat oxidation rates as they are at an intensity that would be reliant on carbohydrate oxidation [154].…”
Section: Green Tea Extractmentioning
confidence: 94%
“…It was demonstrated that giving antioxidant vitamin C or C and E complex reduced PGC-1 a or NRF2 activation and the whole adaptive response was knocked out ([20], [21], [35], [38], [40], [53], [61] (Table 1.)). However, other investigators noted that the adaptive response is much more complex and regulated by multi protein pathways and signaling agents besides ROS, and also that antioxidant treatment did not eliminate the beneficial effects of exercise [13], [25], [28], [55], [58], [64].…”
Section: Introductionmentioning
confidence: 98%